Konstruk Keterlibatan Siswa Pada Proses Pembelajaran Di Kelas - Ningsih, Sustia (Educatio, 2025)
The aim of this research is to parse and understand the construct of student involvement in the learning process in the classroom so that it can improve the quality of education. Definitions, dimensions, measurements, and factors that can support engagement are discussed in this study. Involvement is an important issue that cannot be ignored because of the large influence it has on increasing student achievement and self-development. Engaged students have a certain level of participation and persistence in the learning process, exert effort in class assignments, and show varying levels of interest, motivation, and enjoyment for learning (Fredricks et al., 2004). On the other hand, a disengaged learner is a learner who is bored and anxious or sometimes annoyed to participate in class and performs poorly in various subjects. The method used is qualitative research with descriptive analysis of social phenomena and literature review as reference material for this writing. The results of this research are that student involvement is the time, energy and all action efforts devoted by students in the learning process in class for the purpose of self-development and mastery of knowledge. Engagement has 3 dimensions, namely behavioral, emotional and cognitive. Factors that influence student engagement in class such as teacher support, motivation, and school climate have been widely researched and are recognized as having a significant influence on student engagement in class. The measurement of the student engagement scale is presented for further research material in quantitative form.